Rapid HER2-positive cell detection via high-voltage electroosmotic flow-driven microfluidic SPRi - Zhang, Xinmeng; Jiao, Yue; Yang, Taikang; Xu, Zhourui; Shao, Yonghong; Hou, Jianxun; Xu, Gaixia (Mikrochimica acta (1966), 2025)
The synergy between electroosmotic flow (EOF) and surface plasmon resonance (SPR) offers a transformative approach to overcome diffusion-limited biosensing. However,  existing voltage-driven EOF systems face critical trade-offs between high-voltage requirements and biocompatibility. Here, we present a self-powered electroosmosis-enhanced SPR immunosensor that integrates a triboelectric nanogenerator (TENG) with SPR imaging (SPRi) to achieve ultra-sensitive detection of HER2-positive cancer cells. By leveraging TENG-driven asymmetric alternating electric fields, the developed platform generates electroosmotic vortices that accelerate cellular transport velocity and enhance antigen–antibody binding efficiency, achieving a detection limit of 3 × 10 4 cells/mL—an order of magnitude improvement over label-free SPR methods. Remarkably, the system captures HER2-positive cells within 45 s at a high throughput of cell, the detection speed increased by 20-fold. This performance, combined with label-free operation and biocompatibility, establishes a scalable framework for liquid biopsy applications. Graphical Abstract